The Effect of Language Barriers at Discharge on Pediatric Adenotonsillectomy Outcomes and Healthcare Contact. (July 2021) - Dai, Xi; Ryan, Marisa A.; Clements, Anna Christina; Tunkel, David E.; Links, Anne R.; Boss, Emily F.; Walsh, Jonathan M.
Objective: Effective delivery of discharge instructions and access to postoperative care play a critical role in outcomes after pediatric surgery. Previous studies in the pediatric emergency department suggest that caregivers with language barriers have less comprehension of discharge instructions despite use of interpretation services. However, the impact of language barriers during discharge on surgical outcomes in a pediatric surgical setting has not been studied. This study examined the effect of parental language during discharge on number and mode of healthcare contact following pediatric adenotonsillectomy. Methods: A retrospective cohort study was conducted on children who underwent adenotonsillectomy at a tertiary care pediatric academic medical center from July 1, 2016 to June 1, 2018. Data were collected on consecutive patients with non-English-speaking caregivers and a systematic sampling of patients with English-speaking caregiver. Surgery-related complications and healthcare contacts within 90 days after discharge were collected. Two-tailed t tests, χ 2 tests, and logistic regression were performed to assess the association between parental primary language and incidence of healthcare contact after surgery. Results: A total of 136 patients were included: 85 English-speaking and 51 non-English-speaking. The groups were comparable in age, sex, and comorbidities. The non-English group had more patients with public insurance (86% vs. 56%; P  < .001). Number of encounters and types of complications following discharge were similar, but the non-English group was more likely to utilize the emergency department compared to phone calls (OR, 9.3; 95% CI, 2.3-38.2), even after adjustment for insurance type (OR, 7.9; 95% CI, 1.6-39.4). Conclusion: Language barriers at discharge following pediatric otolaryngology surgery is associated with a meaningful difference in how patients utilized medical care. Interventions to improve comprehension and access may help reduce preventable emergency department visits and healthcare costs.